Tibiotalar cartilage stress corresponds to T2 mapping: application to barefoot running in novice and marathon-experienced runners. Issue 14 (26th October 2019) - Kim, Hyun Kyung; Mirjalili, Ali; Doyle, Anthony; Fernandez, Justin
Abstract: A 3D anatomically-based finite-element foot model was adopted for predicting von Mises stresses within tibiotalar cartilage following 5 km barefoot running. To compare this predicted stress with T2 maps, magnetic resonance scans of the right ankle and plantar pressure were obtained from ten novices and ten marathon-experienced runners before and after running. Following running, tibiotalar cartilage stress was decreased in experienced runners. This corresponded with T2 values that did not change between pre- and post-running suggesting no increase in cartilage fluid levels. In contrast, novices maintained the same level of von Mises stress and this corresponded with a significant T2 increase in tibiotalar cartilage.